SINTESIS Biodegradable Hydrogel dari Amorpophallus Oncophyllus - Ashadi, Reki Wicaksono (Universitas Djuanda Bogor, 2010)
Hydrogel is a colloid gel in which water is dispersed. The production of hydrogel from iles-iles glucomannan in Indonesia has never been studied. Results showed that with the help of sodium phosphate to form a cross bond, iles-iles glucomannan was able to form hydrogel with the capacity to absorb water up to 31% with a yellowish white color. It was expected that this hydrogel would be useful as a medium of transferring medicine into the body as, unlike commercial hydrogel made from polyacrylamide, it is not carcinogenic.